The Inhibition of Macrophage Foam Cell Formation by 9-Cis β-Carotene Is Driven by BCMO1 Activity - Zolberg Relevy, Noa; Bechor, Sapir; Harari, Ayelet; Ben-Amotz, Ami; Kamari, Yehuda; Harats, Dror; Shaish, Aviv (PLOS ONE, 2015)
Atherosclerosis is a major cause of morbidity and mortality in developed societies, and begins when activated endothelial cells recruit monocytes and T-cells from the bloodstream into the arterial wall. Macrophages that accumulate cholesterol and other fatty materials are transformed into foam cells. Several epidemiological studies have demonstrated that a diet rich in carotenoids is associated with a reduced risk of heart disease; while previous work in our laboratory has shown that the 9-cis β-carotene rich alga Dunaliella inhibits atherogenesis in mice. The effect of 9-cis β-carotene on macrophage foam cell formation has not yet been investigated. In the present work, we sought to study whether the 9-cis β-carotene isomer, isolated from the alga Dunaliella, can inhibit macrophage foam cell formation upon its conversion to retinoids. The 9-cis β-carotene and Dunaliella lipid extract inhibited foam cell formation in the RAW264.7 cell line, similar to 9-cis retinoic acid. Furthermore, dietary enrichment with the algal powder in mice resulted in carotenoid accumulation in the peritoneal macrophages and in the inhibition of foam cell formation ex-vivo and in-vivo. We also found that the β-carotene cleavage enzyme β-carotene 15,15’-monooxygenase (BCMO1) is expressed and active in macrophages. Finally, 9-cis β-carotene, as well as the Dunaliella extract, activated the nuclear receptor RXR in hepa1-6 cells. These results indicate that dietary carotenoids, such as 9-cis β-carotene, accumulate in macrophages and can be locally cleaved by endogenous BCMO1 to form 9-cis retinoic acid and other retinoids. Subsequently, these retinoids activate the nuclear receptor RXR that, along with additional nuclear receptors, can affect various metabolic pathways, including those involved in foam cell formation and atherosclerosis.